1995
DOI: 10.1016/0014-5793(95)01093-t
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIIa and the extracellular domains of human tissue factor form a compact complex: A study by X‐ray and neutron solution scattering

Abstract: The four-domain structure of human factor Vlla and the two-domain structure of tissue factor form a tight complex to initiate blood coagulation. By solution scattering, the mean X-ray and neutron radii of gyration Re (which determine macromolecular elongation) were found to be 3.25 nm, 2.13 nm and 3.14 nm (+ 0.13 rim) for factor VIIa, the extracellular region of tissue factor and their complex in that order. The mean cross-sectional radii of gyration Rxs were 1.33 rim, 0.56 nm and 1.42 nm ( + 0.13 nm) in that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
5
26
0
Order By: Relevance
“…The relative orientation of domains is speculative except when multiple close contacts are defined, such as between the second EGF-like and the protease domains. An extended structure of fVIIa has been inferred from X-ray and neutron scattering data (Ashton et al, 1995), but unpublished observations in our laboratory indicate a possible interaction between the Gla and protease domains.…”
Section: Discussionmentioning
confidence: 89%
“…The relative orientation of domains is speculative except when multiple close contacts are defined, such as between the second EGF-like and the protease domains. An extended structure of fVIIa has been inferred from X-ray and neutron scattering data (Ashton et al, 1995), but unpublished observations in our laboratory indicate a possible interaction between the Gla and protease domains.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that the WTFVIIa molecule free in solution has an extended conformation (38) and possesses interdomain flexibility (resulting from Gla-EGF1 and EGF1-EGF2 flexibility) which is reduced on binding to sTF (39). It is likely that both the high affinity of the sTF-WTFVIIa interaction and part of the allosteric promotion of FVIIa activity which results derive from the stabilization by TF of FVIIa inter-and intradomain conformation, requiring some movement of FVIIa domains to orient the large surface involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, the different techniques in these studies yielded different conclusions about the solution structure of the sTF⅐fVIIa complex. In one study, the proteins appeared to be positioned side-by-side in the complex (6), while in the other study, the complex appeared to be substantially more elongated than either of its components (5). Crystal structures of both sTF (7,8) and sTF⅐fVIIa (9) have recently been determined, and in the crystals, sTF and fVIIa are elongated and aligned side-by-side in the sTF⅐fVIIa complex (7)(8)(9).…”
mentioning
confidence: 97%
“…The solution structures of both fVIIa and sTF, the soluble extracellular domain of TF, have been shown, using various biophysical techniques, to be asymmetric or elongated (5,6). However, the different techniques in these studies yielded different conclusions about the solution structure of the sTF⅐fVIIa complex.…”
mentioning
confidence: 99%